Growth Response of Ayapana on inoculation with Bacillus megaterium isolated from different soil types of various agroclimatic zones of Karnataka - C, Sandeep; S, Thejas M; Patra, Sanjeev; Gowda, Tejaswini; Venkat Raman, R; M, Radhika; K, Suresh C; Mulla, S R (Journal of Phytology, 2011)
A study was undertaken to find out the growth response of Ayapana on inoculation with Bacillus megaterium isolated from different soil types of various agroclimatic zones of Karnataka. Bacillus megaterium strains from different soil types of various agroclimatic zones of Karnataka were isolated, identified and confirmed using standard synaptic keys. Ayapana was used as a host plant to study the growth response, biomass and nutrient content. Treatments of Bacillus megaterium isolates from ten different soil types of various agroclimatic zones of Karnataka were given to seedlings of Ayapana. There were significant changes in the plant growth, biomass and nutrient uptake in plants inoculated with Bacillus megaterium when compared to control plants. The parameters such as plant height, number of leaves, shoot and root fresh weight, shoot and root dry weight and nutrient uptake were studied. Plants inoculated with Bacillus megaterium isolates performed well when compared to uninoculated plants. The heights of plants inoculated with Bacillus megaterium isolates were found to be more than uninoculated plants. In plants inoculated with B. megaterium isolates, the height, number of leaves, fresh and dry weight of roots and shoots, nitrogen content, P content and chlorophyll content remained higher than the uninoculated plants. Among ten isolates inoculated, Zone 7 isolate recorded significantly high values in almost all growth parameters chosen for the study. The results suggests that plants inoculated with Bacillus megaterium isolates showed better growth response, biomass yield and nutrient content when compared to uninoculated plants.Â 